Beneficial Effect of Multidomain Cognitive Training on the Neuropsychological Performance of Patients with Early-Stage Alzheimer’s Disease - Anastasia Nousia; Vasileios Siokas; Eleni Aretouli; Lambros Messinis; Athina-Maria Aloizou; Maria Martzoukou; Maria Karala; Charalampos Koumpoulis; Grigorios Nasios; Efthimios Dardiotis (Neural Plasticity)
Background and Purpose. There is an increasing interest in the effect of nonpharmacological interventions on the course of patients with Alzheimer’s disease (AD). The objective of the present study is to determine the benefits of a structured, multidomain, mostly computer-based, cognitive training (MCT) οn the cognitive performance of patients with early-stage AD. Method. Fifty patients with early-stage AD participated in the study. Patients were randomly allocated either to the training program group (n=25) or to a wait list control group (n=25). The training program group received computer-assisted MCT and linguistic exercises utilizing pen and paper supplemented by cognitive-linguistic exercises for homework. The duration of the MCT intervention program was 15 weeks, and it was administered twice a week. Each session lasted for approximately one hour. Objective measures of episodic memory, delayed memory, word recognition, attention, executive function, processing speed, semantic fluency, and naming were assessed at baseline and after the completion of the program in both groups. Results. Analysis showed that in controls, delayed memory and executive function had deteriorated over the observation period of 15 weeks, while the training group improved their performance in word recognition, Boston Naming Test (BNT), semantic fluency (SF), clock-drawing test (CDT), digit span forward (DSF), digit span backward (DSB), trail-making test A (TMT A), and trail-making test B (TMT B). Comparison between the training group and the controls showed that MCT had a significant beneficial effect in delayed memory, naming, semantic fluency, visuospatial ability, executive functions, attention, and processing speed. Conclusions. The study provides evidence of a beneficial effect of MCT with an emphasis on cognitive-language performance of patients with early-stage AD. Considering the limited efficacy of current pharmacological therapies in AD, concurrent computer-based MCT may represent an additional enhancing treatment option in early-stage AD patients.